Role of FHOD1 in tumor cells and tumor immune microenvironment - Yang, Yang; Kang, Zhanting; Cai, Jinlong; Jia, Shan; Fan, Shangqian; Zhu, Huifang (Frontiers in Immunology, 2025)
FHOD 1 (Formin homology 2 domain containing protein 1) is a member of Diaphanous-related formins (DRFs) which contains a GTP-binding domain (GBD), formin homology (FH) 1 and FH 2 domains, a coiled-coil, and a diaphanous-like autoregulatory domain. Studies have shown that FHOD1 can not only regulate intracellular signals in tumor cells but also regulate various components of the tumor microenvironment (TME), such as T cells, B cells, cancer-associated fibroblasts (CAFs), some cytokines. Aberrant expression and dysfunction of the FHOD1 protein play a key role in tumor immunosuppression. Specifically, FHOD1 can impair function of chemokine receptors that are supposed to direct immune cells to localize to the tumor site accurately. As a result of this impairment, immune cells cannot migrate efficiently into TME, thereby impairing their ability to attack tumor cells. In addition, FHOD1 activated signaling pathways within the immune cells abnormally, resulting in their inability to recognize and destroy tumor cells effectively. Therefore, FHOD1 ultimately leads to a state of immunosuppression in TME, providing favorable conditions for the growth and spread of tumor cells. Altogether this review provides an in-depth understanding of the role of FHOD1 in tumor immunosuppression.